Blasting Damage Model of Rock with Initial Damages and Its Application - Pingyuan Yang; Xiaoen Wu; Junhua Chen (Chemical Engineering Transactions, 2018)
Rock is a material subject to initial damage. Rock blasting-induced damage model is the most commonly used constitutive model for numerical simulation of rock blasting. At present, however, most models neglect the effects of initial damage on blasting. To this end, this paper explored the merits and demerits of typical blasting- induced damage models. Then, a rock blasting-induced damage model was proposed by modifying the typical blasting-induced damage models, with the effects of initial damage on damage evolution taken into account. Numbers of parameter in the proposed model are low and all the parameters can be obtained easily from laboratory tests under uniaxial dynamic and static loading. The criterion to determine the fracture state of rock is also given, which is related to initial damage and used for confirming the blasting-induced fracture zone.